GE_GERICHTE C/21446/2012 vom 9. Juni 2015 - GE Cour de justice (2015)
CONTRAT DE TRAVAIL; RÉSILIATION IMMÉDIATE; FIDÉLITÉ; CLAUSE CONTRACTUELLE; PROHIBITION DE CONCURRENCE | CO.337; CO.321d.2; CO.340; CO.340a; CO.321e